PENANAMAN KARAKTER DISIPLIN DALAM MAKAN BERSAMA ANAK USIA DINI USIA 5-6 TAHUN DI RA PERWANIDA 2 PALEMBANG - Azyati Zea, Hazmi; Febriyanti; Murtopo, Ali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the process of developing disciplined character through shared mealtime activities among children aged 5–6 years at RA Perwanida 2 Palembang. The study employs a qualitative approach with a descriptive design to obtain an in-depth understanding of the implementation of discipline habituation at school. Data were collected through participatory observation, semi-structured interviews with teachers and parents, and documentation analysis of the activities. Informants were selected purposively based on their direct involvement in the shared mealtime program. Data analysis was conducted inductively through data reduction, data display, and conclusion drawing. Source and method triangulation were applied to ensure the credibility and validity of the findings. The results indicate that the cultivation of disciplined character during shared mealtime has been implemented quite well through stages such as preparation before eating, compliance with mealtime rules, orderly use of eating utensils, appropriate behavior during meals, independence and responsibility, environmental awareness, time discipline, as well as religious and social attitudes. Supporting factors include teacher role modeling, consistent habituation, clear regulations, parental support, and a positive approach, while inhibiting factors include differences in rules at home and variations in children’s character and emotional conditions. These findings affirm that routine activities designed pedagogically can serve as an effective strategy in early childhood character education and provide conceptual contributions and practical implications for curriculum development in early childhood education institutions.